Analysis of the Effect of the Covid-19 Pandemic on the Import Process of Auxiliary and Raw Materials for Coffee - Burhan Stafrezar; Amin Sadiqin (CV ODIS, 2022)
The free market is being promoted, and the trade era continues to develop globally so that companies that have import-related businesses need knowledge of import procedures and updated regulations related to customs, shipping, banking, taxation, and matters relating to imports. With adequate knowledge, the company can run the business smoothly and minimize the problems that occur in the field. In particular, executives, importers, and purchasing departments are expected to gain a deeper understanding of customs, the concept of international trade, and international taxation. Import is the entry of goods into the customs area. The entry of goods through the delivery of goods mechanism. Shipment is goods that are sent using the postal service provider with the laws and regulations in the postal sector. Courier Service Company (PJT) is a postal service provider that has obtained a business license from the relevant agency to provide mail, document, and package services in accordance with statutory regulations in the postal sector. International trade regulations, start from many economic instruments to achieve economic growth. Coffee is a drink that is loved by the people of Indonesia. Coffee is a drink that may be a daily drink or just to accompany you when you are relaxing. Coffee is also attached to our minds as a drink that interrupts sleepiness.